The Regional Värmland SOM Survey 2018 - SOM Institute, University of Gothenburg (University of Gothenburg, 2019)
In 2018 the SOM Institute carried out the third SOM survey in the region of Värmland. Focus was on issues of public services, regional development and media habits. The survey also related to the relationship to Norway and the opinion on local infrastructure projects. The SOM survey in Värmland is designed in collaboration with Karlstad University.

Purpose:

Study attitudes and behaviours that are linked to local and regional issues and phenomena

2018 genomförde SOM-institutet för tredje gången en SOM-undersökning i Värmland. I fokus ligger frågor om offentlig service, regional utveckling och medievanor. Undersökningen berör också ämnen som relationen till Norge och inställningen till lokala trafikprojekt. SOM-undersökningen i Värmland utformas i samverkan med Karlstads universitet.

Syfte:

Studera attityder och beteenden som är knutna till lokala och regionala frågor och företeelser
SOM-undersökningen i Värmland 2018
Värmlands-SOM 2018
Keywords: housing; boende; occupations; yrken; public sector; offentlig sektor; environment; miljö; trust; förtroende; political interest; politiskt intresse; local government services; kommunal service; public transport; kollektivtrafik; medical care; sjukvård; public services; offentlig service; news; nyheter; income; inkomst; political participation; politiskt deltagande; democracy; demokrati; internal politics; inrikespolitik; political parties; politiska partier; internet use; internetanvändning; politicians; politiker; social participation; socialt deltagande; working conditions; arbetsförhållanden; clubs; föreningar; leisure time activities; fritidsaktiviteter; educational levels; utbildningsnivå; political attitudes; politiska åsikter; CORS; CORS; POLITICS; POLITIK; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; Elections; Val; Political behaviour and attitudes; Politiska beteenden och attityder; Political ideology; Politisk ideologi; Cultural activities and participation; Kulturaktiviteter och deltagande; MEDIA, COMMUNICATION AND LANGUAGE; MEDIA, KOMMUNIKATION OCH SPRÅK; LABOUR AND EMPLOYMENT; ARBETE OCH SYSSELSÄTTNING; Leisure, tourism and sport; Fritid, turism och sport; Social behaviour and attitudes; Socialt beteende och attityder; Social conditions and indicators; Sociala förhållanden och indikatorer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Political Science (Excluding Peace and Conflict Studies); Statsvetenskap (exklusive freds- och konfliktforskning); Media and Communications; Medie-, kommunikations-, och informationsvetenskaper; Media and Communication Studies; Medie- och kommunikationsvetenskap; Other Social Sciences; Annan samhällsvetenskap; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap